2015
DOI: 10.1186/s12974-015-0264-1
|View full text |Cite
|
Sign up to set email alerts
|

MCP-induced protein 1 mediates the minocycline-induced neuroprotection against cerebral ischemia/reperfusion injury in vitro and in vivo

Abstract: BackgroundMinocycline, a broad-spectrum tetracycline antibiotic, has shown anti-inflammatory and neuroprotective effects in ischemic brain injury. The present study seeks to determine whether monocyte chemotactic protein-induced protein 1 (MCPIP1), a recently identified modulator of inflammatory reactions, is involved in the cerebral neuroprotection conferred by minocycline treatment in the animal model of focal cerebral ischemia and to elucidate the mechanisms of minocycline-induced ischemic brain tolerance.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 34 publications
4
46
0
1
Order By: Relevance
“…We also found that minocycline alleviated ischemic stroke-induced brain damage by reducing in- 236 farct volumes and improving neurological disorders and brain edema. These protective effects of minocycline are consistent with previous research [21][22][23] .…”
Section: Discussionsupporting
confidence: 93%
“…We also found that minocycline alleviated ischemic stroke-induced brain damage by reducing in- 236 farct volumes and improving neurological disorders and brain edema. These protective effects of minocycline are consistent with previous research [21][22][23] .…”
Section: Discussionsupporting
confidence: 93%
“…NF-kB activation could be inhibited by minocycline in many diseases. [41][42][43] In our study, air-exposure activated NFkB, and minocycline treatment reduced NF-kB levels, which is consistent with reduced expression of inflammatory mediators. We propose that the inhibition of the NF-kB signaling pathway by minocycline downregulated the expression of inflammatory molecules, such as IL-1b, TNF-a, and MMPs through some underlying mechanisms.…”
Section: Discussionsupporting
confidence: 84%
“…These studies i) demonstrate the beneficial effects of minocycline treatment following hypoxic insult and add to the growing literature of this repurposed therapeutic as a beneficial agent in promoting neuroprotection, neuronal remodeling, and improving neuronal behaviors 64,66,67 ; ii) document the up-regulation of Sox10, HIF1A, and several of the genes associated with proliferation and apoptosis (survivin and YAP), myelination in neurogenic zones and improved cognitive function; and iii) support the possibility of minocycline as a potential transient therapeutic drug in the treatment of the neurodevelopmental handicaps observed in the very premature newborn population. In addition, these studies may aid in the further interpretation of minocycline's effects in the ongoing treatment trials and animal model studies of fragile X syndrome and multiple sclerosis.…”
Section: Minocycline-treated Pups Are Less Anxious and More Exploratomentioning
confidence: 65%